Новий етап досліджень старожитностей Софіївської Борщагівки - Готун, І.А. (Археологічні дослідження в Україні, 2009)
The excavations of the settlement near Sofiivska Borshchahivka on both slopes of the Nyvky River were renewed in 2008 by the Northern expedition. The cultural layer with the sunken parts of the objects contained Ancient Rus ceramics, including fragments of Pontic amphorae, pottery debris of the age of palaeometals, fragments of glass bracelets, plinthoi fragments, knives and other metal wares, hones, etc.